2019
DOI: 10.3390/molecules24244426
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Anticancer Properties of Bioactive Compounds from Sesamum indicum L.—A Review

Abstract: The use of foodstuff as natural medicines has already been established through studies demonstrating the pharmacological activities that they exhibit. Knowing the nutritional and pharmacological significance of foods enables the understanding of their role against several diseases. Among the foods that can potentially be considered as medicine, is sesame or Sesamum indicum L., which is part of the Pedaliaceae family and is composed of its lignans such as sesamin, sesamol, sesaminol and sesamolin. Its lignans h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 157 publications
(173 reference statements)
1
56
0
2
Order By: Relevance
“…F. asafoetida is known to use for the treatment of respiratory problems, including bronchitis, asthma, and whooping coughs [ 39 ]. Additionally, these spice bioactives have exhibited several beneficial activities, including antifungal, antioxidant, hepatoprotective, anti-inflammatory, and have immune-boosting properties [ 16 , [38] , [39] , [40] , [41] , [42] ].…”
Section: Resultsmentioning
confidence: 99%
“…F. asafoetida is known to use for the treatment of respiratory problems, including bronchitis, asthma, and whooping coughs [ 39 ]. Additionally, these spice bioactives have exhibited several beneficial activities, including antifungal, antioxidant, hepatoprotective, anti-inflammatory, and have immune-boosting properties [ 16 , [38] , [39] , [40] , [41] , [42] ].…”
Section: Resultsmentioning
confidence: 99%
“…It then induces the transcription of pro-inflammatory mediators such as iNOS and COX-2. Several studies have shown that anti-inflammatory agents inhibit NF-κB activation by preventing IκB degradation [ 19 , 20 , 21 ]. Thus, we attempted to determine whether 4H-7MTC inhibits IκB phosphorylation and degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Sesamol is a lignin isolated from sesame seeds [7]. Sesamol has many biological functions, which produce anti-inflammatory, antioxidant, and anti-tumor effects [10]. Studies have shown that sesamol could induce apoptosis in cancer cells and inhibit the effects of proliferation and autophagy in lung cancer and colon cancer [11].…”
Section: Discussionmentioning
confidence: 99%
“…Sesamol is a polyphenol lignan isolated from sesame seeds. Sesamol has shown multiple biologically active functions in animal and cellular disease models [10,11]. Sesamol alleviated the expression of inflammatory mediators by suppressing the nuclear factor-κB (NF-κB) and mitogen-activated protein kinase (MAPK) signaling pathways.…”
Section: Introductionmentioning
confidence: 99%